Implementasi Teknologi Business Process Model Notation (BPMN), Teks, Flowchart dan Rich Picture pada Bisnis Startup - Rizqiyatul Khoiriyah; Aan Jelli Priana ((JurTI) Jurnal Teknologi Informasi, 2020)
Abstract - Business processes are very influential in the continuity of a company, including CV. SLC. However, the business processes that occur at CV. SLC has not been well documented so that in practice it is often applied differently by employees. Even though the company also wants to evaluate the performance and performance of the company. From these problems, a description and analysis of business processes are made using several diagrams, namely text form, rich picture flow, flowchart, and Business Process Model Notation (BPMN). The results of the analysis show that understanding business processes is easier to understand if it is modeled with a rich picture/flowchart/notation model compared to verbal / text. However, it is easier to analyze and evaluate in more depth when using the Business Process Model Notation (BPMN). The results of this business process analysis are expected to be implemented following the business reality to improve the performance and performance of CV. SLC.Keywords  -   Business Process, Startup, Rich Picture, Business Process Model Notation (BPMN). Abstrak - Proses bisnis sangat berpengaruh terhadap kelangsungan suatu perusahaan, tidak terkecuali pada CV. Siplho Corporation (SLC). Namun, proses bisnis yang terjadi di CV. SLC belum terdokumentasikan dengan baik, sehingga pada pelaksanaanya seringkali diterapkan secara berbeda oleh pegawai. Padahal perusahaan juga ingin mengevaluasi terhadap kinerja dan performa perusahaannya. Dari permasalahan tersebut maka dibuatlah gambaran dan analisis proses bisnis menggunakan beberapa diagram yaitu bentuk teks, alur rich picture, flowchart dan Business Process Model Notation (BPMN).  Hasil analisis menunjukkan bahwa pemahaman proses bisnis lebih mudah dipahami jika dimodelkan dengan alur gambar/diagram alir/notasi model dibandingkan dengan verbal / teks. Namun lebih mudah dianalisis dan evaluasi lebih mendalam bila menggunakan Business Process Model Notation (BPMN). Hasil analisis proses bisnis ini diharapkan nantinya dapat diimplementasikan sesuai dengan kenyataan bisnis tersebut agar dapat meningkatkan  kinerja dan performa CV. SLC.Kata Kunci - Proses Bisnis, Startup, Rich Picture, Business Process Model Notation (BPMN).